PENINGKATAN KEMAMPUAN MOTORIK KASAR SISWA DENGAN DOWN SYNDROME KELAS III SDLB MELALUI MEDIA ECOPRINT DENGAN TEKNIK POUNDING DI SLB YPPLB PADANG - Kesty, Pika; Tsaputra , Antoni; Marlina , Marlina; Taufan, Johandri (STKIP Pesisir Selatan, 2025)
This study aimed to improve the gross motor skills of a third-grade student with Down syndrome at a special primary school through the use of ecoprint media employing the pounding technique. The research applied a Single Subject Research (SSR) method with an A1–B–A2 design and was conducted at SLB YPPLB Padang. The research subject was one student with Down syndrome. The initial baseline phase (A1) was carried out over five sessions, showing gross motor skill achievement in the range of 15%–20%. The intervention phase (B), implemented for seven sessions using ecoprint media with the pounding technique, demonstrated a gradual improvement in gross motor skills, reaching 40%–100%. In the final baseline phase (A2), conducted over three sessions, the student’s gross motor skills stabilized at 100%. Data were collected through observation and analyzed using visual graph analysis. The findings indicate that ecoprint media with the pounding technique is effective in enhancing the gross motor skills of students with Down syndrome. The novelty of this study lies in the use of ecoprint as a creative and contextual sensorimotor learning medium that aligns with the learning characteristics of students with Down syndrome.